2006
DOI: 10.1063/1.2400105
|View full text |Cite
|
Sign up to set email alerts
|

Demonstration of soot particle resizing in an ethylene flame by small angle x-ray scattering

Abstract: The size distribution of soot nanoparticles in an ethylene flame has been mapped in an in situ small angle x-ray scattering measurement at the European Synchrotron Radiation Facility. It has been seen that an abrupt size distribution change occurs at about a third of the flame’s visible height and this is believed to be due to the oxidation and dehydrogenation of the particles.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
35
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 20 publications
(37 citation statements)
references
References 29 publications
2
35
0
Order By: Relevance
“…The larger particles in the water-added flame, however, have Porod exponent values close to 2 and this indicates that these particles are either configurational flat entities, such as discs as discussed elsewhere by di Stasio [14] or Gaussian linear chains [35]. Our previous studies [15,16] have shown that soot aggregates are quite polydisperse and so it is not possible for us to distinguish between these two forms [35]. We can say, however, that the smaller particles that we have called sub-primaries [14][15][16]34] do cluster together to form larger primary particles with radii of gyration reported in Fig.…”
Section: Resultsmentioning
confidence: 92%
See 2 more Smart Citations
“…The larger particles in the water-added flame, however, have Porod exponent values close to 2 and this indicates that these particles are either configurational flat entities, such as discs as discussed elsewhere by di Stasio [14] or Gaussian linear chains [35]. Our previous studies [15,16] have shown that soot aggregates are quite polydisperse and so it is not possible for us to distinguish between these two forms [35]. We can say, however, that the smaller particles that we have called sub-primaries [14][15][16]34] do cluster together to form larger primary particles with radii of gyration reported in Fig.…”
Section: Resultsmentioning
confidence: 92%
“…5 shows other parameters that can be extracted from the Unified Fitting Function and these are the Porod's exponents (p 1 and p 2 ) of the power-laws describing the behaviour of the scattering intensity at the upper q range of the various size levels. In particular, as described in our previous work [14][15][16]34] the primary particles constituting fractal soot are, in turn, agglomerates of smaller sub-primary particles. In the two-level fitting approach, the Porod exponent p 2 is relative to lower q 0 s (primaries) and p 1 to higher q 0 s (sub-primaries).…”
Section: Resultsmentioning
confidence: 97%
See 1 more Smart Citation
“…that it shows the presence of several different families of particles within the size window of our measurement. Generally for the results presented here, a one level-fit is sufficient and so we do not see signs of aggregation of the nanoparticles as is the case for soot particles in a flame 6,7 or metallic particles formed in a microwave air plasma. 8 Over the many measurements performed between, above and below the electrodes, the mean radius of gyration of the particles determined from fitting the Unified function, fell between 30 and 40 nm.…”
Section: Resultsmentioning
confidence: 99%
“…The large micron sized particles seen here and in previous studies 2 are most likely formed by the ejection of droplets a (The voltage drop between the electrodes during the arc being determined by the electrode material with a value in this case of 25 V irrespective of the initial applied voltage, the energy released into the arc is determined by the current supplied). b In our flame experiments, [6][7][8] we have identified families of nanoparticles of sizes between 10 and 70 nm, though light scattering and electron microscopy studies typically image micron sized structures formed by the aggregation of these nanoparticles.…”
Section: Resultsmentioning
confidence: 99%